2015
DOI: 10.1016/j.cell.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Grain Dispersal System in Barley

Abstract: About 12,000 years ago in the Near East, humans began the transition from hunter-gathering to agriculture-based societies. Barley was a founder crop in this process, and the most important steps in its domestication were mutations in two adjacent, dominant, and complementary genes, through which grains were retained on the inflorescence at maturity, enabling effective harvesting. Independent recessive mutations in each of these genes caused cell wall thickening in a highly specific grain "disarticulation zone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
317
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(342 citation statements)
references
References 43 publications
12
317
2
Order By: Relevance
“…at different stages (i.e., wild, wild-cultivated, domesticated, or a mixture) and hybridized with local wild genetic lineages (24)(25)(26)(27), as well as the continued exploitation of wild cereal stands, should be considered as possible explanations for the protracted establishment of domesticated cereals in southwest Asia.…”
Section: The Regional Evidence For Cereal Domestication (Early/ Middlmentioning
confidence: 99%
See 1 more Smart Citation
“…at different stages (i.e., wild, wild-cultivated, domesticated, or a mixture) and hybridized with local wild genetic lineages (24)(25)(26)(27), as well as the continued exploitation of wild cereal stands, should be considered as possible explanations for the protracted establishment of domesticated cereals in southwest Asia.…”
Section: The Regional Evidence For Cereal Domestication (Early/ Middlmentioning
confidence: 99%
“…The new evidence indicates that predomestication cultivation occurred broadly at the same time in different regions (22,23). Genetic evidence indicates that cultivation practices involved multiple wild progenitor populations located across different regions, and therefore it is not possible to pinpoint the exact origins of domesticated plants (24)(25)(26)(27)(28)(29). Domesticated cereals first emerged during the EPPNB (c. 10.5 ka Cal BP), but they did not become dominant until 1,000 y later (11,12), indicating that domesticated species evolved slowly (21) and that the rates of evolution during domestication were similar to those observed in wild species subject to natural selection (30,31).…”
mentioning
confidence: 99%
“…The genes controlling barley inflorescence architecture and development have only been revealed for a few characters. Major genes that control row type (vrs1 [Komatsuda et al, 2007], intermedium-c [Ramsay et al, 2011], and vrs4 [Koppolu et al, 2013]), the conversion of awns into an extra floret (Hooded; Müller et al, 1995), adherence of the hull to the caryopsis (nud; Taketa et al, 2008), swelling of lodicules conferring open/ closed flowering (cleistogamy/chasmogamy) and spike density (cly1 [Nair et al, 2010] and zeo1 [Houston et al, 2013]), elongation of awns and pistil morphology (lks2; Yuo et al, 2012), suppression of bracts (trd1; Whipple et al, 2010;Houston et al, 2012), spike branching (com2; Poursarebani et al, 2015), and brittleness of the rachis (btr1/btr2; Pourkheirandish et al, 2015) were recently cloned. A large number of additional morphological mutants that influence barley inflorescence development (Forster et al, 2007) also have been described, and the underlying genes need to be identified to reach a more complete understanding of the regulatory pathways controlling barley spike architecture and development (Forster et al, 2007).…”
mentioning
confidence: 99%
“…What is clear is that the appearance and shape of the inflorescence has been under constant visual selection since early domestication and is still ongoing in modern plant breeding due to the impact of inflorescence architecture on crop yield. For instance, in barley (Hordeum vulgare), strong selection has been exerted on spontaneously occurring alleles of nonbrittle rachis1 (btr1) and btr2 that prevent dehiscence of the rachis at maturity (Pourkheirandish et al, 2015), six-rowed spike1 (vrs1) that determines whether the inflorescence exhibits two or six rows of grain (Komatsuda et al, 2007), and nudum (nud) that controls whether the grain is hulled or hull-less (Taketa et al, 2008). Ultimately, knowing all of the genes that control cereal inflorescence architecture will provide targets for understanding and exploiting natural or induced genetic diversity toward improving both yield potential and end-use characteristics.…”
mentioning
confidence: 99%
“…Recently, molecular studies have better elucidated the evolution of this key domestication trait. The paper from Pourkheirandish et al [12] is a milestone in this direction: the authors hypothesize that the anthropogenic selection operated in favor of the mutated forms of a signal transducing receptor and its protein ligand. The two gene products, BTR1 and BTR2, act together to control the cell wall thickening in the disarticulation zone of the rachis node, through molecular mechanisms that are not fully understood.…”
Section: The Brittle Rachismentioning
confidence: 99%